STUDY OF KNOWLEDGE, ATTITUDE, AND PRACTICE OF GENERAL POPULATION OF GUNTUR TOWARD SILENT KILLER DISEASES: HYPERTENSION AND DIABETES - MOUNICA.BOLLU,; Koushik.NALLURI, Kranthi; Prakash, Ambhi.surya; Lohith, Muddana.naga; VENKATARAMARAO, NALLANI (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objectives: The objective was to study the demographic details of hypertensive and diabetic patients and their knowledge, attitude, and practices (KAP) regarding their illness. Methods: We examined KAP on hypertension and diabetes in a sample of 50 adult hypertensive patients and 50 adult diabetic patients aged above 20 years. KAP's were assessed during the period from October 2014 to January 2015. Results: Altogether 50 hypertensive and 50 diabetic patients were enrolled in the study. Most of the respondents in the KAP on hypertension were aged between 31and 40 years (56%) and 94% of the participants knew that hypertension is the disease state whereas in KAP on diabetes 46% are aged in between 31 and 40 years of age, 88% of participants know that the diabetes is a condition in which the body contains increased levels of blood glucose. We observed poor score in attitude and practice part of the questionnaire. It concludes that the responders had good knowledge but poor attitude and practice toward the diseases. Repeated reinforcement and motivation along with health education will definitely bring about a positive change in attitude and practices among the patients. Conclusion: We conclude that the motivation and counseling stressing the importance of lifestyle modifications and self-management is required for the patients suffering with chronic diseases such as hypertension and diabetes. Patient counseling by the clinical pharmacist can play a vital role in imparting education to the diabetic and hypertensive patients. Keywords: Hypertension, Diabetes, Knowledge, Attitude, Practices.